Cloaking nanoparticles with protein corona shield for targeted drug delivery. Issue 1 (December 2018) - Oh, Jun; Kim, Han; Palanikumar, L.; Go, Eun; Jana, Batakrishna; Park, Soo; Kim, Ho; Kim, Kibeom; Seo, Jeong; Kwak, Sang; Kim, Chaekyu; Kang, Sebyung; et al.
Abstract Targeted drug delivery using nanoparticles can minimize the side effects of conventional pharmaceutical agents and enhance their efficacy. However, translating nanoparticle-based agents into clinical applications still remains a challenge due to the difficulty in regulating interactions on the interfaces between nanoparticles and biological systems. Here, we present a targeting strategy for nanoparticles incorporated with a supramolecularly pre-coated recombinant fusion protein in which HER2-binding affibody combines with glutathione-S -transferase. Once thermodynamically stabilized in preferred orientations on the nanoparticles, the adsorbed fusion proteins as a corona minimize interactions with serum proteins to prevent the clearance of nanoparticles by macrophages, while ensuring systematic targeting functions in vitro and in vivo. This study provides insight into the use of the supramolecularly built protein corona shield as a targeting agent through regulating the interfaces between nanoparticles and biological systems. The efficacy of nanoparticles can be significantly inhibited by serum proteins binding to them. Here, the author developed a supramolecularly constructed protein corona on nanoparticles, which minimises interactions with serum proteins to prevent the clearance of these particles by macrophages.